Analysis of the Development and Dynamics of Character Education and Culture of the Indonesian Nation - Permatasari, Mitra; Nurgiansah, T Heru; Erlande, Rike; Randiawan, Randiawan; Hidayah, Eva Nur (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The problem of character education can be seen from various cases such as the failure of an institution in a school institution, the change of ministers that affects the change of curriculum, the existence of deviant behavior in the community environment that has an increasingly negative impact on a nation. This study aims to analyze the problems of the development and dynamics of character education and culture in Indonesia. This study uses literature studies. Data analysis techniques are collecting, reducing, presenting and drawing conclusions. The results of the study show that good character development will encourage generations to grow and commit to doing various things in a better and more progressive direction. To realize the national mission, civic education is very important to be an aspect of study in shaping the personality of citizens. Civic education is regulated as a subject of learning in improving the abilities of each generation to become superior, participatory, honest, noble and responsible human beings. The development of the direction and objectives of character education is very crucial in preventing multidimensional crises and the decline in moral values that can damage the quality of the next generation and the implementation of transformation in an ideal and progressive direction.